Validation of Survey Questions on Counseling About Infant and Young Child Feeding Received by Mothers in Bihar, India. (14th June 2022) - Ashok, Sattvika; Kim, Sunny; Mahapatra, Tanmay; Gokhale, Priya; Munos, Melinda; Heidkamp, Rebecca; Avula, Rasmi
Abstract: Objectives: Scarce data exists on coverage of infant and young child feeding (IYCF) counseling, which includes counseling about breastfeeding and complementary feeding, because few large-scale surveys have included questions to capture the coverage of these essential nutrition interventions. Consequently, maternal report of this information during household surveys has not been validated. We examined the validity of maternal report of IYCF counseling received during home visits and factors associated with response accuracy. Methods: Direct observations of home visits conducted by community workers in 40 villages in Bihar, India, served as the "gold standard" to maternal report of IYCF counseling received during 2-week follow-up surveys (n = 444 mothers with children less than 1 year of age, interviews matched to direct observations). Individual-level validity was assessed by calculating sensitivity, specificity, and area under ROC curve (AUC). Population-level bias was measured using the inflation factor (IF). Multivariable regression models were used to examine factors associated with response accuracy. Results: Actual prevalence of IYCF counseling during home visits was very high (90.1%). Maternal report of any IYCF counseling received in the past 2 weeks had moderate validity (AUC = 0.60, 95% CI: 0.52, 0.67), and population bias was low (IF = 0.90). However, recall of specific counseling messages varied. Maternal report of any breastfeeding, exclusive breastfeeding, and dietary diversity messages had moderate validity (AUC > 0.60), but other child feeding messages had low individual validity. Maternal characteristics associated with response accuracy varied by indicator, but accuracy on reporting of any IYCF counseling received was associated with higher education level and lower mental stress scores. Conclusions: Validity of IYCF counseling coverage varied by indicator but was moderate for several key indicators and performed comparably to other health counseling coverage indicators. Given that counseling is an intervention involving intangible inputs, we consider these modest validity results as positive and suggest that these coverage indicators may be useful for measuring coverage and tracking progress over time. Funding Sources: Bill & Melinda Gates Foundation, through IMPROVE-Coverage and DataDENT, managed by Johns Hopkins University.